The Significance of Figurative Language in Teaching Poetry (مجلة ديالى للبحوث الانسانية, 2023)
Understanding any poems needs a recognition of the figurative language used in order to be able to comprehend the idea and to know what the poet wants to say, reflect, and show. This study aims at finding out:• the importance of poetry in teaching English language for EFL learners and whether figurative language poses a challenge to students of poetry or not.• the type of figurative language that makes it challenging for English as a Foreign Language learners to understand poetry.       75 students in the second grade of the English Department at Diyala University during the academic year 2022–2023 make up the research sample for this study. An achievement test is used to gather data on the poetry proficiency of the students. Eight questions are in the test, two of them are about figurative language and the other two are on three poems by William Shakespeare: The Hind, Spring, and Sonnet 18.     Finally, the test data are analyzed using appropriate statistical techniques. The findings indicated that some of the students have trouble employing metaphorical language when studying poetry.